Human Rights and Maternal Health: Exploring the Effectiveness of the Alyne Decision. Issue 1 (12th April 2013) - Cook, Rebecca J.
<x xml:space="preserve">Abstract</x> This article explores the effectiveness of the decision of the Committee on the Elimination of Discrimination against Women in the case of Alyne da Silva Pimentel Teixeira (deceased) v. Brazil, concerning a poor, Afro‐Brazilian woman. This is the first decision of an international human rights treaty body to hold a state accountable for its failure to prevent an avoidable death in childbirth. Assessing the future effectiveness of this decision might be undertaken concretely by determining the degree of Brazil's actual compliance with the Committee's recommendations, and how this decision influences pending domestic litigation arising from the maternal death. Alternative approaches include: determining whether, over time, the decision leads to the elimination of discrimination against women of poor, minority racial status in the health sector, and if it narrows the wide gap between rates of maternal mortality of poor, Afro‐Brazilian women and the country's general female population. Determining the effectiveness of this decision will guide whether to pursue a more general strategy of judicializing maternal mortality.